The impact of collective trauma on mental health psychology practitioners' wellbeing: Insights gained from Covid-19 - Annita Ventouris; Agata Wezyk; Constantina Panourgia (SSM: Qualitative Research in Health)
Objective: This study aimed at investigating how the pandemic, a collective trauma experience, affected the mental health and wellbeing of Mental Health Psychology Practitioners (MHPPs), along with the strategies employed to maintain positive wellbeing. Method: An exploratory, qualitative research approach was taken, and semi-structured interview data was collected from nine MHPPs and analysed thematically. Results: Three main themes were identified, consisting of two subthemes each, ranging from experiences of vicarious traumatisation, personal vs. professional identity issues, through to the strategies participants employ to maintain their wellbeing. Conclusion: The need for training focusing on collectively traumatic experiences was highlighted by this study’s results. The development of targeted interventions and comprehensive training programmes are essential, including modules on self-care, resilience-building, and maintaining professional boundaries, as they can help this group of practitioners be less susceptible to occupational risks, resulting in better outcomes for both practitioners and their clients.